Single-cell discovery of m6A RNA modifications in the hippocampus - Feng, Shuangshuang; Tellaetxe-Abete, Maitena; Zhang, Yujie; Peng, Yan; Zhou, Han; Dong, Mingjie; Larrea, Erika; Xue, Liang; Zhang, Li; Koziol, Magdalena J. (Genome Research, 2024)
N6-Methyladenosine (m6A) is a prevalent and highly regulated RNA modification essential for RNA metabolism and normal brain function. It is particularly important in the hippocampus, where m6A is implicated in neurogenesis and learning. Although extensively studied, its presence in specific cell types remains poorly understood. We investigated m6A in the hippocampus at a single-cell resolution, revealing a comprehensive landscape of m6A modifications within individual cells. Through our analysis, we uncovered transcripts exhibiting a dense m6A profile, notably linked to neurological disorders such as Alzheimer's disease. Our findings suggest a pivotal role of m6A-containing transcripts, particularly in the context of CAMK2A neurons. Overall, this work provides new insights into the molecular mechanisms underlying hippocampal physiology and lays the foundation for future studies investigating the dynamic nature of m6A RNA methylation in the healthy and diseased brain.